Kinetics of transesterifying multifeedstock oil into biodiesel - Aulia, Haris Numan (Jurnal Polimesin, 2024)
The synthesis of biodiesel is typically performed using homogeneous catalysts and high-temperature transesterification methods. This research aims to investigate the kinetics of transesterification reactions in biodiesel synthesis using a blend of six different types of oils: coconut oil, palm oil, soybean oil, canola oil, sunflower oil, and waste cooking oil. An equal volume of each oil is used to combine the multifeedstock oil, totaling 300 ml. After pretreatment, the multifeedstock oil is heated to 30, 40, 50, and 60°C, combined with a methoxide solution, and blended for a variable number of time intervals of 10, 20, 30, 40, 50, and 60 minutes. After a 24-hour stay, the biodiesel is cleaned and separated from the centrifuge's water content. The biggest conversion, which was attained at 60°C with a reaction time of 60 minutes, was reported in the study's results. Utilizing a base catalyst in accordance with the second-order kinetics of the biodiesel transesterification reaction of multifeedstock oil.